THE SPECIFICITY OF LEGAL RESPONSIBILITY IN THE SYSTEM OF LOCAL SELF-GOVERNMENT (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article discusses issues related to the study of the organization and activities of local governments, legal responsibility in the local government system.
Keywords: local self-government, bodies of local self-government, officials of local self-government, bodies and officials of local self-government, representative bodies of local self-government, executive bodies of local self-government, legal responsibility in the system of local self-government.